Fabrication and evaluation of the performance of Co/CoNiZnAg nanoporous structures as a good candidate for using as anode catalyst in a hydrazine fuel cell. (19th September 2019) - Hosseini, Mir Ghasem; Abdolmaleki, Mehdi; Daneshvari-Esfahlan, Vahid
ABSTRACT: The goal of this work is synthesis a new nanoporous Co/CoNiZnAg catalyst by the leaching-galvanic replacement (LGR) process as a highly active and good durable electrocatalyst towards hydrazine oxidation reaction in an alkaline medium. The morphology and elemental analysis of fabricated electrocatalysts were investigated using scanning electron microscopy (SEM) and energy-dispersive X-ray spectroscopy (EDX), respectively. The results showed that a nanoporous structure for Co/CoNiZnAg coatings. Electrocatalytic activity and stability of these catalysts were estimated using cyclic voltammetry and chronoamperometry methods. The hydrazine oxidation peak current density of this coating towards hydrazine oxidation is higher than that on a smooth silver electrode. The results confirmed that the Co/CoNiZnAg electrocatalyst has a better electrocatalytic activity and enhanced stability. As a result, Co/CoNiZnAg electrocatalyst can be considered a good candidate for using as an anode catalyst in direct hydrazine fuel cells (DHFCs).